Educational activities in the role of government nurseries and its relationship to some variables (Journal Of Educational and Psychological Researches, 2011)
The skill of management educational activities gradually grow with the experience, but they differ from personal skill educator to another, because each style nanny personally and the way to work. There educator and active movement and vitality that look like happiness and clear during the implementation of the activity, and the other runs educational activities quietly, efficiently and without emotion and clear (dry, 2001: p. 274). And the stage of childhood is one of the most important stages that are based upon the future life as a whole because the man also confirmed by the School of analysis psychological is the son of his childhood and the best example to us what the Holy Prophet Muhammad (peace be upon him): (Every child is born to the manner born his parents make him a Jew or a Christian or a Magian), where the show saying (peace be upon him) that the good in human authentic and evil viewer. So it is best if the child's upbringing and guidance in the right direction, it will build a strong future. Since the nursery so you must complement the House be directed educational activities to serve the children and led to righteousness. (Moses, 1993, p. 22).   A goal of research is to measure the educational activities in the role of government nurseries (research sample) and measuring the difficulties and obstacles in the implementation of educational activities, according to (the number of years of service, qualifications, age and training courses). The limits of the current search all kindergartens governmental organizations in the city of Baghdad, was the research sample (18, director and 36 assist and 46 educator, became the sample (100) for the academic year 2010 / 2011. Use the Search descriptive analytical method was prepared questionnaire to measure the educational activities, reaching paragraphs-resolution final ( 40 paragraph) included five areas (activities, kinesthetic, linguistic, religious, moral, Asahahn and social) took paragraphs three alternatives (high agreement, approval of a moderately, but the approval.) weights (3.2, 1) respectively, the highest degree of the questionnaire ( 40-120) and the average Varzi (80 degrees). were performed for the identification of validity and reliability. identified the researcher card to observe the ways of implementing the activities consisting of (19 paragraph). researcher used a number of statistical methods to interpret the results. Chirba results to the lack of statistically significant differences due to the variables research. The reason is that the role of incubators government very little, and their buildings and wide and prepared well and equipped with all the comforts of tools and games for the implementation of all educational activities there. The most important proposals is to further research on educational activities to include all the provinces. The most important recommendations is to increase the numbers the role of government nurseries, to include all areas of Baghdad and increase the number of jams ineach Jdhana, in order to interest children.